Neuroleptic malignant syndrome due to ziprasidone: a case report - Huarcaya-Victoria, Jeff (2019)
Neuroleptic malignant syndrome is a rare and potentially fatal drug adverse reaction, usually associated with antipsychotics. Signs and symptoms include: fever, muscle rigidity, altered mental status and autonomic dysfunction. Laboratory findings are nonspecific, however the presence of leukocytosis and elevated creatinine phosphokinase are frequent findings. We present the case of a 51-year-old male patient from Lima with a medical history of pulmonary tuberculosis and schizophrenia that comes to our hospital with psychotic symptoms. After being treated with ziprasidone, administered by intramuscular injection presents with typical symptoms of neuroleptic malignant syndrome. Knowing the clinical features and the pathophysiology of this syndrome will allow us to better approach the condition. Due to its infrequent presentation, it may not be considered within the differential diagnosis, which could be harmful to the patient.